Reduction of Bias and Light Instability of Mixed Oxide Thin-Film Transistors - Mallory Mativenga; Jae Gwang Um; Jin Jang (Applied Sciences, 2017)
Despite their potential use as pixel-switching elements in displays, the bias and light instability of mixed oxide semiconductor thin-film transistors (TFTs) still limit their application to commercial products. Lack of reproducible results due to the sensitivity of the mixed oxides to air exposure and chemical contamination during or after fabrication hinders any progress towards the achievement of stable performance. Consequently, one finds in literature several theories and mechanisms, all justified, but most of them conflict despite being on the same subject matter. In this study, we show that under an optimized fabrication process, which involves the in situ passivation of a mixed oxide semiconductor, we can reduce the bias and light instability of the mixed-oxide semiconductor TFTs by decreasing the semiconductor thickness. We achieve a negligible threshold voltage shift under negative bias combined with light illumination stress when the mixed oxide semiconductor thickness is around three nanometers. The improvement of stability in the thin mixed-oxide semiconductor TFTs is due to a reduced number of oxygen-vacancy defects in the bulk of the semiconductor, as their total number decreases with decreasing thickness. Under the optimized fabrication process, bulk, rather than interfacial defects, thus seem to be the main source of the bias and light instability in mixed oxide TFTs.